Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A lipopolysaccharide‐dependent phage infects a pseudomonad phytopathogen and can evolve to evade phage resistance - Suzanne L. Warring; Lucia M. Malone; Jay Jayaraman; Richard A. Easingwood; Luciano A. Rigano; Rebekah A. Frampton; Sandra B. Visnovsky; Shea M. Addison; Loreto Hernandez; Andrew R. Pitman; Elena Lopez Acedo; Torsten Kleffmann; et al. (Environmental Microbiology, 2022)
Bacterial pathogens are major causes of crop diseases, leading to significant production losses. For instance, kiwifruit canker, caused by the phytopathogen Pseudomonas syringae pv. actinidiae ( Psa ), has posed a global challenge to kiwifruit production. Treatment with copper and antibiotics, whilst initially effective, is leading to the rise of bacterial resistance, requiring new biocontrol approaches. Previously, we isolated a group of closely related Psa phages with biocontrol potential, which represent environmentally sustainable antimicrobials. However, their deployment as antimicrobials requires further insight into their properties and infection strategy. Here, we provide an in‐depth examination of the genome of ΦPsa374‐like phages and show that they use lipopolysaccharides (LPS) as their main receptor. Through proteomics and cryo‐electron microscopy of ΦPsa374, we revealed the structural proteome and that this phage possess a T = 9 capsid triangulation, unusual for myoviruses. Furthermore, we show that ΦPsa374 phage resistance arises in planta through mutations in a glycosyltransferase involved in LPS synthesis. Lastly, through in vitro evolution experiments we showed that phage resistance is overcome by mutations in a tail fibre and structural protein of unknown function in ΦPsa374. This study provides new insight into the properties of ΦPsa374‐like phages that informs their use as antimicrobials against Psa .